Immunoglobulins or Antibodies: IMGT® Bridging Genes, Structures and Functions - Marie-Paule Lefranc; Gérard Lefranc (Biomedicines, 2020)
IMGT®, the international ImMunoGeneTics® information system founded in 1989 by Marie-Paule Lefranc (Université de Montpellier and CNRS), marked the advent of immunoinformatics, a new science at the interface between immunogenetics and bioinformatics. For the first time, the immunoglobulin (IG) or antibody and T cell receptor (TR) genes were officially recognized as ‘genes’ as well as were conventional genes. This major breakthrough has allowed the entry, in genomic databases, of the IG and TR variable (V), diversity (D) and joining (J) genes and alleles of Homo sapiens and of other jawed vertebrate species, based on the CLASSIFICATION axiom. The second major breakthrough has been the IMGT unique numbering and the IMGT Collier de Perles for the V and constant (C) domains of the IG and TR and other proteins of the IG superfamily (IgSF), based on the NUMEROTATION axiom. IMGT-ONTOLOGY axioms and concepts bridge genes, sequences, structures and functions, between biological and computational spheres in the IMGT® system (Web resources, databases and tools). They provide the IMGT Scientific chart rules to identify, to describe and to analyse the IG complex molecular data, the huge diversity of repertoires, the genetic (alleles, allotypes, CNV) polymorphisms, the IG dual function (paratope/epitope, effector properties), the antibody humanization and engineering.